Ibn Khafajah And the power of nature's beauty (Journal of the College of Basic Education, 2022)
We find that our poet Ibn Khafaja Al-Andalusi (451-533 AH) was looking for beauty in everything, but he finally settled in the bosom of nature, whose features he had drawn through his poetry. It is worth noting that he dazzled the recipient in his time and after his time until he was described as (the heavens) because his poetry is different artistic paintings, depicting the aesthetics of that nature, and it must be noted in this field that we researched this